A Comprehensive Systematic Review of The Role of Genetic Factors in Brain Tumor Development - Muhammad Rizal Nur Fauzi; Almira Fadhila Az Zahra (International Medical Journal Corp. Ltd, 2025)
Introduction: Brain tumors represent a significant source of morbidity and mortality worldwide, with primary gliomas and meningiomas being the most common types. While environmental factors play a role, there is compelling evidence that genetic predisposition substantially contributes to their etiology. This systematic review aims to synthesize the current evidence on the role of germline genetic factors in the development of primary brain tumors. Methods: A comprehensive systematic review was conducted following predefined screening criteria. Data from 80 peer-reviewed sources, including genome-wide association studies (GWAS), meta-analyses, case-control studies, and Mendelian randomization analyses, were extracted and synthesized. The focus was on studies reporting quantitative associations between genetic variants and brain tumor risk, with an emphasis on germline factors, distinct tumor subtypes, and diverse populations. Results: The analysis identified multiple robust genetic susceptibility loci. Key findings include the strong, subtype-specific associations of loci such as TERT (5p15.33) for overall glioma, RTEL1 (20q13.33) and EGFR (7p11.2) for glioblastoma (GBM), and CCDC26 (8q24.21) for non-GBM gliomas (Melin et al., 2017). Significant ethnic heterogeneity was observed, particularly in DNA repair gene polymorphisms (e.g., ERCC2 rs13181 and XRCC1 rs1799782) and growth factor genes (e.g., EGF rs4444903) (Chen et al., 2014; Tavares et al., 2020). Furthermore, distinct genetic architectures were revealed based on sex, age, and molecular subtypes (e.g., IDH mutation status). Mendelian randomization studies highlighted causal links between immune traits, metabolic factors, and glioma risk, while heritability analyses estimated that approximately 25% of glioma risk is attributable to common genetic variants, with only 6% explained by currently known loci (Kinnersley et al., 2015; Ostrom et al., 2021). Discussion: The genetic landscape of brain tumors is characterized by remarkable complexity, involving subtype specificity, population diversity, and intricate biological pathways such as telomere maintenance, DNA repair, and immune regulation. These findings reconcile previously reported inconsistencies and underscore the need for stratified analyses. Conclusion: Genetic factors are pivotal in brain tumor susceptibility. Future research must prioritize large, diverse cohorts and integrative multi-omics approaches to elucidate the remaining heritability and translate these findings into improved risk prediction, prevention strategies, and targeted therapies.